PENGGUNAAN MEDIA REPLIKA TANGAN DALAM MENINGKATKAN PEMAHAMAN MATERI SISTEM GERAK PADA SISWA KELAS VI SEKOLAH DASAR - Novia Ramdhani; Fitria Nurulaeni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of using a hand replica model on the understanding of the musculoskeletal system among sixth-grade elementary school students, addressing the issue of low comprehension resulting from instruction that remained abstract and lacked concrete learning aids. A quantitative approach with a quasi-experimental design was employed, utilizing pre-tests and post-tests for both experimental and control groups. The results demonstrated an improvement in student understanding within the experimental group, evidenced by an increase in the mean score from 42.69 to 77.31 and a hypothesis test significance value of 0.03 (p < 0.05), indicating a significant effect of using the hand replica model. Furthermore, the N-Gain score of 0.6175 (61.75%) fell into the moderate category, signifying reasonable effectiveness. Consequently, the use of the hand replica model proved effective in enhancing student understanding and fostering a learning environment that is interactive, meaningful, and student-centered.